THE IMPACT OF WHATSAPP TOWARD UAD UNDERGRADUATE STUDENTS’ BEHAVIOR IN LEARNING PROCESS - Rahaded, Umar; Puspitasari, Erna; Hidayati, Dian (International Journal of Educational Management and Innovation, 2020)
WhatsApp is one of the social media that is used to communicate in the learning process. At present, students cannot be separated from their daily activities away from this social media. This opportunity can be utilized as well as possible by the students. This research was conducted to find out of using WhatsApp toward undergraduate students’ behavior in the teaching and learning process. This study was descriptive qualitative research. The data were analyzed using descriptive analysis technique. The data were collected using interviews, observation, and documentation. The aim of this study to analyze the impact of WhatsApp toward undergraduate students’ behavior and to analyze students’ behavior in their learning process. The result of this research showed that are a positive impact on student behavior as it affects the learning process as, students’ sharing knowledge, student preparation for class, attention, student participation in class, student learning, desires to take additional classes or in subject matter and the negative impact such as, students are more focused.